Doctor Consultation Duration on Patient Satisfaction at The Internal Medicine Outpatient Clinic - Iskandar, Muhamad Taufan; Sundari, Sri (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Long waiting times for healthcare services are one of the causes of patient dissatisfaction. The average waiting time for patient services at the Internal Medicine outpatient clinic is 280 minutes with the average duration of a doctor’s consultation being only 6 minutes. Nowadays, patients can decide for themselves whether long waiting times for short doctor consultations are worth the effort. This study aimed to determine patient satisfaction based on the duration of the doctor’s consultation. This research was conducted at the Internal Medicine Clinic using a quantitative observational analytical research design with a cross-sectional data collection method using a questionnaire. The patient satisfaction questionnaire uses a 1-5 Likert scale, while the doctor consultation duration questionnaire uses actual recording in minutes. The respondents for this study were 139 respondents based on epi-info software calculations with a confidence interval of 95%, and the sampling method used consecutive sampling. The research results were analyzed using SPSS version 21 with the chi-square analysis method. The duration of the doctor consultation, with an average of 6 minutes, does not affect patient satisfaction (p-Value 0.842). There are many other factors that can influence patient satisfaction, not limited to the duration of the doctor consultation.